RESERVOIR CHARACTERIZATION AND STATIC MODELLING OF PLIOCENE LIMESTONE MUNDU FORMATION IN NAE FIELD, EAST JAVA BASIN - Wibowo, Heru
Nae field is an oil and gas production field from the Mundu Formation in the East Java Basin. The study combines the two main studies which is the reservoir characterization then followed by constructing the static reservoir model. The work intends to describe the reservoir characterization, depositional facies and rock type grouping facies of limestone reservoir. Static modeling is intended to build a model of depositional environment, rock type and three-dimensional model of reservoir properties i.e. porosity, permeability, and water saturation based facies modeling that have been made. Geological modeling aims to attain a updated static geological model that is more accurate to respond the variation of productivity in every segment of the Nae Field. This study also aims to provide development strategy by determining a new infill development well. Carbonate deposition setting is in an unrimmed carbonate ramp environment that can be divided into three depositional facies i.e. inner shelf, middle shelf, and outer shelf. Studies are conducted through the rock-type descriptions (megascopical and petrographical observation of rock texture and rock fabric, and petrophysical analysis (porosity and permeability data), combined with an approach to global hydrolic element method (GHE). Rock types are grouped into four namely Rock type 1 (foraminiferal wackestone), Rock type 2 (foraminiferal packstone), Rock type 3 (foraminiferal packstone/grainstone), and Rock type 4 (foraminiferal grainstone). The lateral geometry of the deposition environment and rock types are built using sequence stratigraphical concept framework. Property modeling i.e. porosity, permeability, and water saturation model are constructed based on the study of reservoir characterization and facies modeling of deposition facies and rock type. Modeling results indicated a consistency relationship between facies models and model properties. In the depositional environment with a relatively shallow depth and high energy such as inner shelf, will be deposited Rock type 3 and 4 that is composed by packstone and grainstone. Consequently it will naturally have high porosity and permeability. Meanwhile, in the deeper and quieter depositional environment for instance outer shelf tends to be deposited sediment that represents the character of Rock type 1 and Rock type 2. The qualitative comparison between production data and static model showing a realibility relationship of facies deposition geometry, rock type distribution and petrophysical properties Wells with good fluids production (for example Nae-5 and Nae5) has a reservoir formed on the inner shelf environment to middle shelf that dominated by Rock type 3 and 4. In contray, wells with low production (Nae-7 and Nae-8) are wells that is producing from Rock type 2 and 1 (the outer shelf limestone facies). One new development infill well location is succefully determined on the basis of modeling results.